2010
DOI: 10.1002/em.20631
|View full text |Cite
|
Sign up to set email alerts
|

In vitro micronucleus screening of pharmaceutical candidates by flow cytometry in Chinese hamster V79 cells

Abstract: We previously reported a high concordance of in vitro micronucleus (MNvit) results obtained by flow cytometry to the known cytogenetic activity often commercially available compounds mentioned as validation compounds in an early draft of the OECD MNvit TG487 [Bryce et al., 2010; Organization for Economic Co-operation and Development(OECD), 2007]. The current study investigated this method in Chinese hamster V79 cells with pharmaceutical compounds of unknown genotoxic potential. Twenty-five compounds from sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A metaphase spread from donor BM3164 Quantum with chromosomal loss (45,XY,–3) is illustrated in Figure 5A–C, and a metaphase cell from donor BM3164 TCPS with chromosomal gain (47,XY,+ 18) is shown in Figure 5D,E. Structural chromosomal abnormalities were rare (2% in TCPS and 3% in Quantum) and were represented by chromosomal break [46,XY,chrb(10)(p11.2) in Quantum] and reciprocal translocations [46,XY,t(3;6)(q29;p21.1) and 46,XY,t(1;13)(p32;q21) in TCPS, 46,XY,t(16,21) (q13;q21), 46,XY,t(1;15)(p33;q26) and 46,XY, t(3;13)(p15;q31),t(6;7)(p23;q32) in Quantum]. Reciprocal translocations are illustrated in Figure 6A–D for donor BM3164 Quantum and Figure 6E–H for donor 5 TCPS.…”
Section: Resultsmentioning
confidence: 99%
“…A metaphase spread from donor BM3164 Quantum with chromosomal loss (45,XY,–3) is illustrated in Figure 5A–C, and a metaphase cell from donor BM3164 TCPS with chromosomal gain (47,XY,+ 18) is shown in Figure 5D,E. Structural chromosomal abnormalities were rare (2% in TCPS and 3% in Quantum) and were represented by chromosomal break [46,XY,chrb(10)(p11.2) in Quantum] and reciprocal translocations [46,XY,t(3;6)(q29;p21.1) and 46,XY,t(1;13)(p32;q21) in TCPS, 46,XY,t(16,21) (q13;q21), 46,XY,t(1;15)(p33;q26) and 46,XY, t(3;13)(p15;q31),t(6;7)(p23;q32) in Quantum]. Reciprocal translocations are illustrated in Figure 6A–D for donor BM3164 Quantum and Figure 6E–H for donor 5 TCPS.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we have investigated only one high throughput high IVMN approach using a cell fluorescence-based platform. Other high throughput IVMN approaches exist, such as flow-cytometry based techniques which have been developed in a multitude of cell lines, TK6, V79 and CHO’s for example [ [47] , [48] , [49] ]. In these high throughput approaches 10,000 cells can be analysed in as little as 2 min vs. 600 cells in 15 min using traditional scoring approaches [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other high throughput IVMN approaches exist, such as flow-cytometry based techniques which have been developed in a multitude of cell lines, TK6, V79 and CHO’s for example [ [47] , [48] , [49] ]. In these high throughput approaches 10,000 cells can be analysed in as little as 2 min vs. 600 cells in 15 min using traditional scoring approaches [ 48 ]. Furthermore, it was reported that automated scoring could reduce man hours per study by 70 %, increase data turn around by 50 % and due to the assessment of large cell numbers, the variability of the automated technique could be lowered too [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of these methods are included in Supplementary Data S1. Methods for high-content imaging of Cryptosporidium proliferation in HCT-8 cells (Love et al, 2017), QPatch hERG (Danker and Moller, 2014), rat cardiovascular screening (Banfor et al, 2016), in vitro micronucleus assay (Nicolette et al, 2011), the 24-well Ames screening assay, kinome profiling (Goedken et al, 2015), Nluc C. parvum in infected adult IFN-γ KO mouse efficacy (Hulverson et al, 2017), Gastroplus (Simulations Plus, Inc., Lancaster, CA, USA) modelling of efficacy and GI tissue and lumen exposures (Arnold et al, 2017), and IOWA-II strain C. parvum in infected neonatal calf efficacy (Schaefer et al, 2016) have all been previously described. All LC-MS/MS analytes were measured with an Acquity ultra performance liquid chro6 matography (UPLC) system in tandem with a Xevo TQ-S mass spectrometer (Waters, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%